Plantain foliar emission and its relationship with floral differentiation. - Vargas-Calvo, Alfonso; Acuña-Chinchilla, Pablo; Valle-Ruiz, Henry (Agronomía Mesoamericana, 2015)
The objective of this study was to determine the relationship between foliar emission and floral differentiation in False Horn plantains. Four studies were carried out on the Caribbean coast of Costa Rica between November 2000 and January 2014. Recoded variables were type and number of emitted leaves. In Study I (tall and dwarf cultivars, first ratoon) leaf emission was similar among tall (P=0.2417) and dwarf (P=0.5735) cultivars and between both of them (P=0.4170). In Study II (cv. Harton tall, plant crop) the vegetative phase of the meristem was observed in 100% of plants until the emission of leaf 21. The highest percentages of plants in which the meristem was in transition stages was 55%, 60%, 72% and 60%, and occurred in plants with 24, 25, 26 and 27 leaves, respectively. In Study III (cvs. Hartón tall and Hartón dwarf, second ratoom) differentiation was observed from leaf 20 in 10% and 60% of plants of tall and dwarf cultivars, respectively. A 100% of the dissected plants were in transition or at different stages of the reproductive phase by the time they reached leaf 24. In Study IV (Harton tall, second ratoon) it was not possible to find a relationship between the floral differentiation phase